Development of a cambrian back-arc basin in the North Qilian orogenic belt: New constraints from gabbros in Yushigou ophiolite - Tian, Hao; Liu, Xijun; Wu, Hao; Li, Dechao; Liu, Xiao; Song, Qi; Li, Zhenglin; Liu, Pengde; Hu, Rongguo; Yang, Qijun (Frontiers in Earth Science, 2023)
The North Qilian orogenic belt, as the northern branch of the original Tethys tectonic domain, is important for reconstructing the tectonic evolution of the ancient Tethys. However, the tectonic history of the North Qilian orogenic belt remains controversial. This study addresses this issue from a geochemical perspective. In this study, a comprehensive analysis of the geochronology, whole-rock geochemistry, clinopyroxene mineral geochemistry, zircon Ti crystallization temperature, and gabbromagma temperature and pressure in the Yushigou ophiolite of the North Qilian orogenic belt was conducted to provide constraints on its tectonic evolution. Laser ablation inductively coupled plasma mass spectrometry zircon U-Pb dating results reveal that the gabbros have ages of 519±3 Ma and 495±4 Ma, belonging to the Cambrian period. Most of the studied gabbros exhibited geochemical characteristics of tholeiitic basaltic rocks with normal mid-ocean ridge basalt and island arc tholeiite dual geochemical affinities. The gabbros are interpreted to have formed by a high degree of partial melting of the depleted mantle spinel lherzolite. These results suggest that the back-arc basin of the North Qilian tectonic belt may have evolved to a relatively mature stage from 519–495 Ma. Overall, this study contributes to our understanding of the tectonic evolution of the North Qilian orogenic belt through geochemical analyses.